Adults Hospitalized With Coronavirus Disease 2019 (COVID-19)—United States, March–June and October–December 2020: Implications for the Potential Effects of COVID-19 Tier-1 Vaccination on Future Hospitalizations and Outcomes. (12th May 2021) - Sami, Samira; Tenforde, Mark W; Talbot, H Keipp; Lindsell, Christopher J; Steingrub, Jay S; Shapiro, Nathan I; Ginde, Adit A; Douin, David J; Prekker, Matthew E; Erickson, Heidi L; Brown, Samuel M; Peltan, Ithan D; et al.
Abstract: Background: Because of the increased risk for severe coronavirus disease 2019 (COVID-19), the Advisory Committee on Immunization Practices (ACIP) initially prioritized COVID-19 vaccination for persons in long-term care facilities (LTCF), persons aged ≥65 years, and persons aged 16–64 years with high-risk medical conditions when there is limited vaccine supply. We compared characteristics and severe outcomes of hospitalized patients with COVID-19 in the United States between early and later in the pandemic categorized by groups at higher risk of severe COVID-19. Methods: Observational study of sampled patients aged ≥18 years who tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and admitted to one of 14 academic hospitals in the United States during March–June and October–December 2020. Demographic and clinical information were gathered from electronic health record data. Results: Among 647 patients, 91% met ≥1 of the following risk factors for severe COVID-19 [91% March-June (n = 434); 90% October–December (n = 213)]; 19% were LTCF residents, 45% were aged ≥65-years, and 84% had ≥1 high-risk condition. The proportion of patients who resided in a LTCF declined significantly (25% vs 6%) from early to later pandemic periods. Compared with patients at lower risk for severe COVID-19, in-hospital mortality was higher among patients at high risk for severe COVID-19 (20% vs 7%); these differences were consistently observed between March–June and October–December. Conclusions: Most adults hospitalized with COVID-19 were those recommended to be prioritized for vaccination based on risk for developing severe COVID-19. These findings highlight the continued urgency to vaccinate patients at high risk for severe COVID-19 and monitor vaccination impact on hospitalizations and outcomes.